‘The invention of curatorship in Australia’, Review of: Recent Past. Writing Australian Art by Daniel Thomas, edited by Hannah Fink and Steven Miller, Sydney: Art Gallery of New South Wales/Thames and Hudson, 1 December 2020 - Jaynie Anderson (Journal of Art Historiography, 2021)
Daniel Thomas’s first volume of collected writings is a small sample from about a thousand articles written over seventy years. From the time Thomas returned to Australia from Oxford to become the first curator of Australian art at the Art Gallery of New South Wales in 1958, he emerged as a leading figure in the Australian art world. Then as the inaugural head of Australian art at the newly established National Gallery, Canberra (1978-1984), and as Director of the Art Gallery of Australia (1984-1990), he developed curatorship as a profession, created national collections with remarkable acquisitions, developed provenance research and much more. This book is essential reading for anyone who writes on Australian art.